Two Sides Of The Same Coin? A Panel Data Approach To The Innovation-Standard Relationship - Wayoro, Didier; Nonguierma, Wilfried; Parkouda, Michelle (Journal of Standardisation, 2024)
Previous studies have shown an ambivalent relationship between standards and innovation while emphasizing the need to clarify the relationship and uncover their possible causal link. This paper revisits the standard-innovation relationship with the ISO 9001 standard, and patents applications as indicators of standards and innovation, respectively. Using a panel dataset of 81 countries covering the period 1993-2019, we find that ISO 9001 certification is positively associated with innovation. Our fixed-effects and system GMM estimates show that doubling the number of ISO 9001 certificates obtained at the national level increases innovation by 1.3-2.2%. The results vary according to the edition of the standard and the countries’ level of development, whereby developed countries seemed to benefit more from the international quality management standards. The paper also suggests that official development assistance (ODA) may be a vehicle through which wealthier countries can help developing ones harness the benefits of standardization.